Interaksi Sosial Budaya Timur-Barat Novel Liak Ngakak Karya Putra Mada: Kajian Sosiologi Sastra - Nova Sandityawati, Ni Putu; Suarsa, I Made; Jumadiah, Sri (Humanis; Volume 16. No. 1. Juli 2016, 2017)
This study analyzed the novel LiakNgakak by Putra Mada using sociological approach that focuses on the study of sociology of literature and social interaction. The issues that were analyzed in this study are (1) How is the structure of novel LiakNgakak including its characterization, plot, and setting. (2) How is the social interaction of East-West culture in novel LiakNgakak viewed from the aspect of sociology of literature. The theories used in this study were the structural theory and the sociology of literature theory. Structural theory was used to analyze the intrinsic elements, while the sociological theory of literature was employed to assess the social interaction of East-West culture in novel LiakNgakak . To analyze the intrinsic elements, a theory proposed by Nurgiyantoro was used, while on the other hand, a theory proposed by Damono, John LuwisGillin and John Philip Gillin was used to analyze the social cultural interaction of the East-West culture.